2017
DOI: 10.1038/srep44950
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste in apple: the role of sorbitol, individual sugars, organic acids and volatile compounds

Abstract: Sweetness is one of the main drivers of consumer preference, and thus is given high priority in apple breeding programmes. Due to the complexity of sweetness evaluation, soluble solid content (SSC) is commonly used as an estimation of this trait. Nevertheless, it has been demonstrated that SSC and sweet taste are poorly correlated. Though individual sugar content may vary greatly between and within apple cultivars, no previous study has tried to investigate the relationship between the amount of individual sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 49 publications
14
117
2
Order By: Relevance
“…It has been reported that apples that bloom earlier tend to taste sweeter . Sweet taste in apples might be correlated with free sugar content . Little information is available about the nutritional components, such as free sugars and organic acids, in these new apple cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that apples that bloom earlier tend to taste sweeter . Sweet taste in apples might be correlated with free sugar content . Little information is available about the nutritional components, such as free sugars and organic acids, in these new apple cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…The values of sorbitol content observed by researchers, related to a cultivar of fruit. Aprea et al [30] noted values between 1.3 and 12.9 g/kg (average 5.5 g/kg) in 17 different cultivar/accessions. Wider range of the level of sorbitol has been reported by Wang et al [29] -between 0.0 and 15.3 g/L (average 4.3 g/L) -the values marked in 62 apple cultivars.…”
Section: Sugar Profilesmentioning
confidence: 97%
“…Recently, the importance of aroma components in the characteristics of flavor and preference in apple has been widely recognized. Aprea et al [11] reported that sorbitol content correlated with perceived sweetness better than any other single sugar or total sugar content. Furthermore, their predictive model based on partial least squares regression included not only SSC but also volatile compounds and revealed that several volatiles are possibly contributing to flavor.…”
Section: Analysis Of Volatile and Water-soluble Compoundsmentioning
confidence: 99%
“…Furthermore, the rich watercore trait has become a breeding target with the aim of increasing the sweet flavor in apple [10]. Aprea et al [11] proposed that apple breeding programs must take into account factors such as volatile compounds, texture parameters, minor components, and information from sensory panels. However, perceived sweetness is difficult to be described because it is always perceived in combination with other sensory properties, which influence its evaluation.…”
Section: Introductionmentioning
confidence: 99%